Extended Bacteria Culture-Based Clustering Identifies a Phenotype Associating Increased Cough and Enterobacterales in Stable Chronic Obstructive Pulmonary Disease - Muggeo, Anaëlle; Perotin, Jeanne-Marie; Brisebarre, Audrey; Dury, Sandra; Dormoy, Valérian; Launois, Claire; Ancel, Julien; Mulette, Pauline; de Champs, Christophe; Deslée, Gaëtan; Guillard, Thomas (Frontiers in Microbiology, 2021)
Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease characterized by airflow limitation. This chronic respiratory disease represents the third leading cause of worldwide death. Alteration of the airway microbiota has been reported to be associated with exacerbation frequency in COPD. But its role on the symptoms in patients at stable state is still incompletely described. This study aimed to determine whether bacteria isolated in sputum can be associated with clinical features of COPD patients within stable state. Our study highlights, for the first time, that altered microbiota with Enterobacterales is associated with pejorative clinical symptoms in stable COPD patients. The airway microbiota of 38 patients was analyzed using an extended culture approach and mass spectrometry identification. Clusters analysis by principal coordinate analysis (PCoA) of the bacterial communities showed that the patients could be classified into three distinct clusters in our cohort. The clusters showed no differences in phylum’s proportions, but one of them was associated with a high prevalence of Enterobacterales (71.4% in cluster 1 vs 0% in cluster 3), loss of microbiota diversity and higher bacterial load (107 vs 105 CFU/mL, respectively), and characterized by predominant cough and impact on mental health. These novel findings supported by further studies could lead to modifying the processing of COPD sputum in the everyday practice of clinical microbiology laboratories.